Ancestral sequence reconstruction as a tool to study the evolution of wood decaying fungi - Ayuso-Fernández, Iván; Molpeceres, Gonzalo; Camarero, Susana; Ruiz-Dueñas, Francisco Javier; Martínez, Angel T. (Frontiers in Fungal Biology, 2022)
The study of evolution is limited by the techniques available to do so. Aside from the use of the fossil record, molecular phylogenetics can provide a detailed characterization of evolutionary histories using genes, genomes and proteins. However, these tools provide scarce biochemical information of the organisms and systems of interest and are therefore very limited when they come to explain protein evolution. In the past decade, this limitation has been overcome by the development of ancestral sequence reconstruction (ASR) methods. ASR allows the subsequent resurrection in the laboratory of inferred proteins from now extinct organisms, becoming an outstanding tool to study enzyme evolution. Here we review the recent advances in ASR methods and their application to study fungal evolution, with special focus on wood-decay fungi as essential organisms in the global carbon cycling.